Principal leadership in fostering an effective school culture in primary education - Ervin Alberthina Dimara; Priadi Surya; Tarso Tarso (Curricula: Journal of Curriculum Development, 2025)
Principal leadership has a strategic role in creating a conducive, character-based, and competitive learning environment. This study was conducted because some elementary schools still lack optimal conditions for building an effective school culture. The purpose of this study is to describe the leadership style of the principal and his role in developing an effective school culture at SD Inpres 7 Sorong Regency. The approach used is qualitative with a case study type. Data collection techniques include observation, in-depth interviews, and documentation. Data were analyzed using Miles and Huberman's model, which involves three stages: data reduction, data presentation, and conclusion. The results of the study showed that the principal applied a situational leadership style, predominantly using a dominant participatory approach, and occasionally employed a delegative and authoritarian style. The principal fulfills the role of EMASLIM (Educator, Manager, Administrator, Supervisor, Leader, Innovator, Motivator) through strategies such as strengthening the 5S culture, implementing school regulations, utilizing fingerprints, and offering moral mentoring programs. Adaptive and collaborative leadership has proven to be the key to forming an effective school culture and supporting the achievement of the school's vision and mission.   Abstrak Kepemimpinan kepala sekolah mempunyai peran yang strategis dalam menciptakan lingkungan belajar yang kondusif, berkarakter, dan kompetitif. Penelitian ini dilakukan karena masih terdapat sekolah dasar yang belum optimal dalam membangun budaya sekolah yang efektif. Tujuan penelitian ini adalah untuk mendeskripsikan gaya kepemimpinan kepala sekolah dan perannya dalam mengembangkan budaya sekolah yang efektif di SD Inpres 7 Kabupaten Sorong. Pendekatan yang digunakan adalah kualitatif dengan jenis studi kasus. Teknik pengumpulan data meliputi observasi, wawancara mendalam, dan dokumentasi. Data dianalisis dengan menggunakan model Miles dan Huberman, melalui tahapan reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa kepala sekolah menerapkan gaya kepemimpinan situasional dengan gaya dominan partisipatif, dan kadang-kadang menggunakan gaya delegatif dan otoriter. Kepala sekolah menjalankan peran EMASLIM (Educator, Manager, Administrator, Supervisor, Leader, Innovator, Motivator) melalui strategi seperti penguatan budaya 5S, peraturan sekolah, sidik jari, dan program pendampingan moral. Kepemimpinan yang adaptif dan kolaboratif telah terbukti menjadi kunci untuk membentuk budaya sekolah yang efektif dan mendukung pencapaian visi dan misi sekolah. Kata Kunci: budaya sekolah efektif; kepemimpinan kepala sekolah; sekolah dasar